Crucial areas of the economic analysis of public cancer care - D. A. Andreev; K. I. Polyakova; A. A. Zavyalov; T. N. Ermolaeva; A. G. Fisun; A. D. Ermolaeva; V. A. Dubovtseva; T. E. Maksimova (Фармакоэкономика, 2020)
Introduction. The economic aspects of providing cancer care to the public attract increasing attention of scientists, economists, physicians and other healthcare professionals. Currently, the healthcare economics of oncological institutions is defined as part of the national economy that implements cancer care programs and provide a wide range of medical and pharmaceutical services to the public.Aim. The study was conducted as part of the program for improvement of financial spending in order to facilitate cancer care for Moscow residents. The aim of this study was to identify the crucial areas of the cost analysis and thus improve the public health service.Materials and methods. We used the methodology of targeted and consistent search of the literature. The data search and analysis was carried out using the US National Medical Library (PubMed database), National Electronic Library (e-LIBRARY, Russia), and other Internet resources. Whenever possible, articles on the most common and socially significant types of cancer (breast, colon, prostate, lung etc.) were selected. In addition, we focused on significant studies conducted either on the national or international level.Results and discussion. In principle, the structure of total costs is determined by the health policy regarding the cancer care system. Six main areas of oncological care that require careful economic analysis have been identified: those are prevention, oncoscreening, diagnosis, treatment, rehabilitation, and palliative care. In order to implement the economic goals of the healthcare system, the cost of cancer treatment should be discussed. The relevant programs are expected to be based on 1) prevalence and incidence; 2) impact on health; 3) results of the integrative methodological approach to cancer treatment; 4) implementation of comprehensive measures of medical and social assistance; 5) use of financial mechanisms and their impact on economic indicators.Conclusion. The set of measures related to the direct costs as identified in this study include the development, planning and provision of cancer care. These specific features of the direct cost analysis are important for organizing medical care in oncological institutions.